Validity and reliability of an instrument for assessing microteaching in chemical biological sciences - Gonzaléz-Meléndez, Roberto Cruz (2023)
Introduction: Microteaching is a technique that allows the improvement of teachers’ didactic skills with their students in the classroom, and in order to evaluate the performance of this technique it is necessary to have valid and reliable instruments. Objective: To determine the validity and reliability of the Microteaching Assessment Questionnaire (MAQ) of teachers of the QFB Career at the FES Zaragoza, UNAM. Method: The MAQ was applied to a non-probabilistic sample of 124 students after a 20-minute class. Results: An instrument of 49 questions distributed in three factors was obtained with a total variance of 51.57%, according to the Exploratory Factor Analysis, and Cronbach’s alpha of 0.961. Discussion: It is considered that the validity and reliability obtained make the MAQ a useful instrument for students to evaluate the teaching skills of teachers in the QFB career.